Flexible conductive blend of natural rubber latex with PEDOT:PSS - Boratto, Miguel H. [UNESP]; Nozella, Natan L. [UNESP]; Ramos, Roberto A. [UNESP]; Da Silva, Rafael Aparecido [UNESP]; Graeff, Carlos F. O. [UNESP] (AIP Publishing, 2020)
Natural Rubber Latex (NRL) obtained from Hevea brasiliensis is a biocompatible electrically insulating material with exceptional mechanical properties. Poly(3,4-ethylene dioxythiophene) poly(styrene sulfonate), PEDOT:PSS, on the other hand, is a biocompatible highly conductive organic material with poor flexibility. We hereby introduce a blend of NRL/PEDOT:PSS (N/P). This study involved different N/P volume ratios and temperatures of curing aiming at an optimal combination of good flexibility and conductivity. Low-temperature annealing, at 60 °C, dries and cures the blend in a few minutes and improves its tensile strength and conductivity. The blend can stretch more than 700% of its initial length and presents a good gauge factor and small resistance variation (R/R0) for ΔL/L0 of up to 100%. Among the different N/P concentrations, the membranes of an N/P ratio of 1/4 and those thermally cured have the most promising conductive flexible properties for bioelectronic applications.